2009
DOI: 10.1557/proc-1184-gg01-05
|View full text |Cite
|
Sign up to set email alerts
|

Automated diffraction tomography combined with electron precession: a new tool forab initionanostructure analysis

Abstract: Three-dimensional electron diffraction data was collected with our recently developed module for automated diffraction tomography and used to solve inorganic as well as organic crystal structures ab initio. The diffraction data, which covers nearly the full relevant reciprocal space, was collected in the standard nano electron diffraction mode as well as in combination with the precession technique and was subsequently processed with a newly developed automated diffraction analysis and processing software pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Each measurement was carried out using precession electron diffraction (PED) for a further reduction of dynamical scattering effects and a more appropriate reflection integration. [13,14] Detailed information about the data collection is given in Table 1. According to reflection conditions and intensity distribution, the space groups Pnma (no.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each measurement was carried out using precession electron diffraction (PED) for a further reduction of dynamical scattering effects and a more appropriate reflection integration. [13,14] Detailed information about the data collection is given in Table 1. According to reflection conditions and intensity distribution, the space groups Pnma (no.…”
Section: Resultsmentioning
confidence: 99%
“…62) with unit-cell data of a = 18.331(2), b = 8.086(1), c = 13.851(1) and Z = 16. The compound is a highly condensed layer phosphate with a degree of con- powder X-ray diffraction fail, the new method of automated electron diffraction tomography (ADT) [13][14][15] has been developed over the last few years. It has been shown that ADT is an effective way for ab initio structure solution on the basis of electron diffraction data.…”
Section: Introductionmentioning
confidence: 99%
“…At first the technique was tested on well known and beam-stable phases, as barite (BaSO 4 , [4]) and calcite (CaCO 3 , [5]). After the establishment of a suitable experimental protocol, the structure solution of these phases was demonstrated to be routinely reproducible.…”
Section: E Mugnaioli U Kolbmentioning
confidence: 99%
“…To overcome all these problems, a new technique for automated collection of nano electron diffraction data from non-oriented zones was developed: automated diffraction tomography (ADT, [1,2]). This technique was recently coupled with precession electron diffraction (PED, [3]), allowing the structure solution of even very complex inorganic and hybrid organic-inorganic phases.At first the technique was tested on well known and beam-stable phases, as barite (BaSO 4 , [4]) and calcite (CaCO 3 , [5]). After the establishment of a suitable experimental protocol, the structure solution of these phases was demonstrated to be routinely reproducible.…”
mentioning
confidence: 99%
“…the distance the Ewald sphere cuts the reflection from its centre [31]. In order to take the excitation error better into account by an integration of the full reflection intensity, PED can be coupled with ADT [41,42]. The resulting data sets proved to be of high quality and in the last two years several complicate inorganic and organic structures have been solved ab initio by direct methods with a fully kinematic approach [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%